SOCIALIZATION OF COMPLAINT SERVICE APPLICATION MANAGEMENT IN MEKARJAYA VILLAGE, CIANJUR - Muslim, Buhori (Jurnal Pengabdian Masyarakat AbdiMas, 2025)
The village, as the closest government institution to the community, has the responsibility to provide good and prompt services. In Mekarjaya Village, Campaka, Cianjur, an information system called SISimpe has been developed as a platform for monitoring complaints and submissions. This system was built as a testament to the concern of the UNPI Cianjur academic community for the harmony of Mekarjaya Village residents. The idea for developing the application originated from the findings of the Community Service Team's survey, which indicated that Mekarjaya Village needed a communication platform and had issues with conveying complaint information or proposal submissions, especially during the selection of village officials, where there was a lot of unverified and often misleading information, even tending towards hoaxes. Therefore, in this follow-up service activity, based on the existing platform and the problem of misinformation being spread by irresponsible parties, the team is conducting outreach for the SISimpe application as an effort to foster a responsible character in communicating all information. This community service compares and observes the behavior of society in using the application and its impact on their character, through questionnaires and direct interviews with the application users. The results show a significant change in the behavior of the community, becoming more responsible in delivering information.